THE PRECARIOUS STATUS OF THE INDUS DOLPHIN (PLATANISTA MINOR) BETWEEN GUDDU AND SUKKUR BARRAGES IN 1999 (Biological Sciences - PJSIR, 2003)
The history of ecological studies on the Indus River Dolphin (Platanista minor) is reviewed and constraints on counting the dolphins are critically assessed. In spite of its limitations the downstream transect count technique is the best practical solution at the present time. It is suggested that more reliable objective recording techniques need to be developed in order to assess accurately the size of the population and the use of recording hydrophones (PODS) is suggested. Since the Dolphin Reserve was set up in the early 1970s, the number of dolphins steadily increased. Although since the mid-1990s the number seems to have reached a plateau but this may be due to the variability of the counts.